Association of Increased Oncostatin M with Adverse Left Ventricular Remodeling in Patients with Myocardial Infarction - Adnan Riaz, Sabeen Khalid, Amna Ihsan, Aneela Shabbir, Ahmad Ashar Ghuman, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Myocardial infarction is the leading cause of death worldwide. Patients suffering from myocardial infarction with a ST-elevated segment termed as STEMI experience high risk of death and these patients report recurrent attacks even more as compared to other MI patients. Objective: The goal of this study was to check that either oncostatin M (OSM) can be used as a biomarker for the evaluation of myocardial infarction Study design: This control-experimental study was conducted in Biochemistry department of the Islam Medical College, Sialkot. Materials and methods: The study included 35 STEMI patients admitted in hospital, their oncostatin M level after 24 h of the onset of disease was calculated. The oncostatin M level after 6 months was later on analyzed. Electrocardiography was performed for all patients. The serum level was studied properly to look for level of biomarkers. The review board and ethical committee of the hospital approved the study. Results: OSM level was increased after 24h of the onset of the disease. There was reduction in the level of OSM when measured after 6 months but still the levels suggested that OSM was detectable in the serum and can be used as a biomarker for myocardial infarction. Conclusion: High levels of OSM in the serum after 24h can be attributed to its link with development of adverse LV remodeling among patients suffering from myocardial infarction. The OSM levels were decreased eventually but it was still high even after 6 months of the onset. Keywords: CAD, oncostatin M, myocardial infarction, STEMI